Anti-NMDA receptor autoimmune encephalitis in childhood and viral causes: a literature review (Research, Society and Development, 2023)
Introduction: Autoimmune encephalitis corresponds to a group of diseases in which there is production of antibodies against neuronal autoantigens, the main one being anti-NMDA receptor encephalitis. Objective: This review seeks to elucidate the etiologies, clinical picture and diagnostic criteria associated with this pathology in the pediatric population, collaborating with early diagnosis and reducing morbidity and mortality. Method: It consists of a literary review, with data collection in the bases: Scielo, UpToDate and PubMed. Complete articles were included, in English, Spanish and Portuguese and published from 2000 onwards. Duplicate works, without a defined diagnosis, dealing exclusively with neoplasms or with animal experiments were excluded. Totaling a selection of 47 articles. Results and Discussion: Encephalitis due to anti-NMDA antibodies has an incidence of about 0.85 cases per million children from the second to the tenth year of life. Classically, they have prodromes such as fever, diarrhea or respiratory symptoms and after acute or subacute presentation of psychiatric symptoms, seizures, cognitive impairment, lowered level of consciousness and autonomic dysfunction. The diagnosis is based on clinical criteria and laboratory tests. Initial treatment consists of the use of acyclovir, due to the fact that herpes simplex infection is the most common viral etiology in the pediatric population, followed by corticosteroid therapy and/or immunoglobulin. It has a favorable prognosis when therapeutic measures are started early. Conclusion: New studies elucidating the pathophysiology related to anti-NMDA receptor encephalitis caused by the Epstein-Bar virus and COVID-19 are needed. With a variable clinical presentation, this pathology presents itself as a diagnostic challenge.